Transformasi Digital dalam Administrasi Publik dan Dampaknya terhadap Kesadaran Politik Ekonomi: Analisis Pendekatan Kualitatif dalam Connected Community - Tekat Sukomardojo; Ryan Aldiansyah Akbar; Zaenal Aripin; Fakhry Amin; Endang Fatmawati (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Digital transformation affects various conditions and aspects of human life. One of the areas affected is public administration. This research aims to see and explore how digital transformation and public administration and the impact it has on the political and economic awareness of people who have started to be connected by the presence of technology. This research was carried out using a qualitative approach to be able to see how digital transformation in public administration can affect the political economy of society. The results of this study found that there was a significant impact on political economy awareness and the way government works as a whole as a result of digital transformation in public administration. This is because the existence of public transformation can increase efficiency, transparency and participation for the community. In the context of political economy awareness, digital transformation enables wider and inclusive participation from society. Through digital platforms, the public can provide input, express opinions, and participate in relevant discussions.